2020
DOI: 10.37311/jhsj.v2i1.4556
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Pemeriksaan Deteksi Dini Kanker Serviks Metode Inspeksi Visual Dengan Asam Asetat

Abstract: Penelitian ini bertujuan untuk mengetahui faktor yang berhubungan dengan pemeriksaan deteksi dini kanker serviks dengan menggunakan metode tes Inspeksi Visual dengan Asam Asetat (IVA). Penelitian ini merupakan penelitian kuantitatif dengan pendekatan crossectional untuk mengetahui faktor yang berhubungan dengan deteksi dini kanker serviks metode IVA tes di Puskesmas Kenali Besar Kota Jambi tahun 2019. Populasi penelitian ini adalah Wanita Usia Subur (WUS) yang berkunjung di Ruang KB/Kespro dari bulan Maret sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…in women of childbearing age, all have had sexual intercourse which means they also have risk factors for cervical cancer [23] The results of statistical tests obtained a value of 0.001 so that the Ha hypothesis is accepted, it can be concluded that there is a significant relationship between attitudes and WUS participation in the early detection of cervical cancer using the IVA method. These results are relevant to research in 2020 which states that, based on statistical tests, a p value of <0.05 was obtained, which means that there is a significant relationship between attitudes and early detection of cervical cancer using the IVA test method [22].An attitude has not automatically manifested in the form of practice. For the realization of an attitude to become a real action (practice), supporting factors or enabling conditions are needed.…”
Section: Relationship Between Attitude and Early Detection Of Cervical Cancer Methods Ivamentioning
confidence: 71%
See 1 more Smart Citation
“…in women of childbearing age, all have had sexual intercourse which means they also have risk factors for cervical cancer [23] The results of statistical tests obtained a value of 0.001 so that the Ha hypothesis is accepted, it can be concluded that there is a significant relationship between attitudes and WUS participation in the early detection of cervical cancer using the IVA method. These results are relevant to research in 2020 which states that, based on statistical tests, a p value of <0.05 was obtained, which means that there is a significant relationship between attitudes and early detection of cervical cancer using the IVA test method [22].An attitude has not automatically manifested in the form of practice. For the realization of an attitude to become a real action (practice), supporting factors or enabling conditions are needed.…”
Section: Relationship Between Attitude and Early Detection Of Cervical Cancer Methods Ivamentioning
confidence: 71%
“…Based on the results of the study showed that a good attitude towards early detection of cervical cancer with the IVA method was 80 (55.2%) good. These results are relevant to the study in 2020, which showed that the percentage of people who had never carried out an early detection examination of cervical cancer using the IVA test method had a good attitude (73.5%) [22].This is because attitude is a reaction or ISSN: 2722 -4015 http://ijstm.inarah.co.id response that is still closed from a person to a stimulus or object. The manifestation of that attitude cannot be directly seen, but can only be interpreted beforehand from closed behavior.…”
Section: Relationship Between Attitude and Early Detection Of Cervical Cancer Methods Ivamentioning
confidence: 72%
“…5 Data Dinas Kesehatan Provinsi Jambi melaporkan tahun 2016-2018 terdapat 743 (1,34%) IVA-test positif dari 55.570 WUS yang diperiksa, dan kasus terbanyak terdapat di Kota Jambi yaitu sebanyak 140 (18,84%). 6 Puskesmas Koni adalah salah satu puskesmas non-perawatan di Kota Jambi dan merupakan Fasilitas Kesehatan Tingkat Pertama BPJS Kesehatan. Beralamat di Jalan Diponegoro Nomor 53 Kecamatan Pasar Jambi, Kota Jambi, telepon 0741-05911148, email puskesmas_koni@yahoo.com.…”
Section: Pendahuluanunclassified
“…Precancerous lesions can be caught early and prevented from developing into cervical cancer. Alternatively, the cervix if treatment is immediately done (Herawati et al, 2020). Another factor that causes mothers not to perform VIA examinations is the lack of maternal knowledge and attitudes toward the examination of the mother (Widayanti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The IVA test is a visual acidic basic analysis utilizing a vinegar arrangement (3-5% acidic corrosive) on the cervix and seeing various changes after the spread. The point is to see the presence of dysplasia cells as an evaluating strategy for cervical malignant growth (Herawati et al,2020). While Pap Smear sensitivity and specificity were 90.6% and 70.6%, VIA sensitivity, and specificity increased to 65.6% and 75.5%, respectively.…”
Section: Introductionmentioning
confidence: 99%